Ceramics : a potter's handbook - Nelson, Glenn C. (New York : Holt, Rinehart and Winston, 1971)
Ceramics is a studio handbook for the practicing potter, intended to provide essential information on the history of man's accomplishment in clay and glazes and on the means of transforming raw, wet clay into fired and finished pieces. Prepared as a guide for the amature as well as a reference volume for more experienced artists and craftsmen, Ceramics offers, first, an introduction to the art of ceramics through critical review of significant historical and modern works selected from cultures around the world. The text then follows a sequence of technical explanations that begins with the properties and preparation of clay and proceeds through the means of forming clay, the principles of ceramic form and design, and the possibilities for decoratioin and glazing, to the activity and environment of the professional potter, the operatin and construction of kilns, and a survey of the equipment appropriate for the complete ceramic studio. Concluding the book are appendices offering more technical and tabular data, sources of supplies, and a bibliography of published references. A glossary sharpens the usage of technical terms already defined on their introduction in the text. ... cover.
Bibliography: p. 329-332.
Keywords: Ceramics